Tumor necrosis factor, interleukin-1 and interleukin-8 mediate the nociceptive activity of the supernatant of LPS-stimulated macrophages - S. M. Thomazzi; R. A. Ribeiro; D. I. Campos; F. Q. Cunha; S. H. Ferreira (Mediators of Inflammation)
It has been suggested that the supernatant of LPSstimulated macrophages (macrophage nociceptive factor, MNF) promotes nociception in mice. Intraperitoneal administration of MNF induced dose-related writhing, which reached a plateau between 18 and 26 min after injection and decreased within 60 min. The release of MNF was inhibited by the pretreatment of the macrophages with cycloheximide, a protein synthesis inhibitor, or with the glucocorticoid dexamethasone. Cyclooxygenase inhibitors, such as indomethacin or paracetamol, had no effect. The MNF-induced nociception was inhibited in a dose-related manner by pretreatment of the animals with indomethacin, paracetamol or dexamethasone. Pretreatment of the animals with the sympatholytics guanethidine and atenolol partially reduced the MNF nociception, which was abolished by the combination of guanethidine or atenolol with indomethacin. The preincubation of MNF with antisera against TNF-α, IL-1 or IL-8 partially inhibited its nociceptive effect. Intraperitoneal injection of a mixture of the recombinants cytokines TNF-α, IL-1 and IL-8 mimicked MNF nociception. The individual injection of these cytokines was unable to induce the nociceptive effect. In conclusion, our data suggest that the nociceptive activity of the supernatant of LPSstimulated macrophages is explained by the presence of TNF-α, IL-1 and IL-8, the nociceptive activity of which (in mice) seems to be due to the release of cyclooxygenase and sympathetic metabolites.